Development of PBL-based E-Worksheet for 8th Grade Students’ Critical Thinking Skills - Subekti, Yunti Fahrulia; Andriyani, Andriyani (Universitas Ahmad Dahlan, 2023)
This research developed e-worksheet based on Problem Based Learning (PBL) to improve the problem-solving abilities of grade VIII students. The development method uses the ADDIE model, with validation instruments, student responses, as well as pretest and posttest. The validation results show a high level of validity of the e-worksheet. Student responses to E-worksheet are also positive. Pretest and posttest analysis showed a significant increase in problem solving abilities. However, this increase is still limited due to time constraints.